Dampak Gaya Kepemiminan, Budaya Organisasi, dan Motivasi Kerja Terhadap Kinerja Pegawai di Dinas Lingkungan Hidup Kota Surakarta - Monyka Dayu Astuti; Khabib Alia Akhmad; Esti Dwi Rahmawati (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
A leadership style that pays little attention to the fate of its members can lead to low employee performance. By understanding the influence of leadership style, organizational culture, and work motivation on employee performance, steps can be taken to improve organizational effectiveness and employee performance. This study aims to determine whether Leadership Style (X1), Organizational Culture (X2), and Work Motivation (X3) affect Employee Performance (Y) at the Dinas Lingkungan Hidup Kota Surakarta. This study used 51 respondents with quantitative methods. Data collection through questionnaires distributed to employees of the Dinas Lingkungan Hidup Kota Surakarta. Sampling is done by non probability sampling technique with purposive sampling type. Data were analyzed using multiple linear regression analysis and hypothesis testing. The results in this study are Leadership Style, Organizational Culture, and Work Motivation simultaneously have a positive and significant effect on the Performance of Employees of the Dinas Lingkungan Hidup Kota Surakarta. And partially Leadership Style (X1), Organizational Culture (X2), and Work Motivation (X3) have a positive and significant effect on Employee Performance (Y).